A Comprehensive Immune Cell Atlas of Cystic Kidney Disease Reveals the Involvement of Adaptive Immune Cells in Injury-Mediated Cyst Progression in Mice. Issue 4 (April 2022) - Song, Cheng J.; Li, Zhang; Ahmed, Ummey Khalecha Bintha; Bland, Sarah J.; Yashchenko, Alex; Liu, Shanrun; Aloria, Ernald J.; Lever, Jeremie M.; Gonzalez, Nancy M.; Bickel, Marisa A.; Giles, Cory B.; Georgescu, Constantin; et al.
Significance Statement: It is widely accepted that injuries to cilia mutant mice accelerate the rate of cystic kidney disease. However, cellular factors that accelerate cystic disease are unknown. By performing single-cell RNA sequencing of all CD45 + immune cells, we found that the subtypes and gene expression profiles of adaptive immune cells are significantly altered among non-injured, aged cystic mice; injury-accelerated cystic mice; and noncystic controls. Surprisingly, deletion of all adaptive immune cells reduced cystic disease in the injury-accelerated model but had no effect on cystic disease in the non-injured model. This differential rescue may be due to unique adaptive immune cell subtypes and ligands that are only present in the injury-accelerated model of cystic disease. Visual Abstract: Abstract : Background: Inducible disruption of cilia-related genes in adult mice results in slowly progressive cystic disease, which can be greatly accelerated by renal injury. Methods: To identify in an unbiased manner modifier cells that may be influencing the differential rate of cyst growth in injured versus non-injured cilia mutant kidneys at a time of similar cyst severity, we generated a single-cell atlas of cystic kidney disease. We conducted RNA-seq on 79, 355 cells from control mice and adult-induced conditional Ift88 mice (hereafter referred to as cilia mutant mice) that were harvested approximately 7 months post-induction or 8 weeks post 30-minute unilateral ischemia reperfusion injury. Results: Analyses of single-cell RNA-seq data of CD45 + immune cells revealed that adaptive immune cells differed more in cluster composition, cell proportion, and gene expression than cells of myeloid origin when comparing cystic models with one another and with non-cystic controls. Surprisingly, genetic deletion of adaptive immune cells significantly reduced injury-accelerated cystic disease but had no effect on cyst growth in non-injured cilia mutant mice, independent of the rate of cyst growth or underlying genetic mutation. Using NicheNet, we identified a list of candidate cell types and ligands that were enriched in injured cilia mutant mice compared with aged cilia mutant mice and non-cystic controls that may be responsible for the observed dependence on adaptive immune cells during injury-accelerated cystic disease. Conclusions: Collectively, these data highlight the diversity of immune cell involvement in cystic kidney disease.